The Diction of Punishment and Rhetorical Effects in Surah Al-Lahab: A Stylistic Study - Al Farisi, Salman; Khabibulloh, Muhammad Irkham; Habibie, Habil (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Surah Al-Lahab is one of the chapters in the Qur’an that delivers a strong message about punishment, conveyed through direct language and powerful rhetorical style. This article specifically discusses how diction choices and rhetorical effects related to the theme of punishment are used in the surah. The study employs a qualitative method with a stylistic approach to describe the linguistic features that intensify the threat conveyed in the verses of Surah Al-Lahab. The focus of the analysis is on the use of curse-laden diction and stylistic devices such as metaphor, repetition, and deep visual symbolism. The results show that the diction of punishment in this surah not only creates an emotional atmosphere but also clearly defines the ideological stance toward the cursed figure. Thus, the stylistic strength of this surah functions not only as an aesthetic element but also as an effective and impactful medium for conveying the message of Islamic preaching (da’wah).